PENERAPAN NILAI-NILAI â€œKALO SARAâ€ PADA KEPEMIMPINAN KEPALA SMA NEGERI 1 TANGGETADA KOLAKA - Hadijah, Andi (Pascasarjana Universitas Negeri Makassar, 2015)
The study aimed at examining (i) the implementation strategy of Kalo Sara values on the principal’s leadership at SMN 1 Tanggetada, (ii) the impact of the implementation of Kalosaravalues on the principal’s leadership at SMN 1 Tanggetada, and (iii) the supporting and inhi biting factors of the implementation afKala Sara values on the principal’s leadership at SMN 1 Tanggetada. The study was conducted at SMAN 1 Tanggetada in Tanggetadasubdistrct of Kolaka district. The study employed descriptive qualitative. The data sources of the study were the principal, vice-principal, Head of Administrative Departement, and 2 teachers. Data were collected through observation, interview, and documentation. Data collection was analyzed qualitativery by conducting data reduction, data presentation, and data validation. The results of the study reveal that the implementation of Kalo Sara values on the principal’s leadership at SMAN 1 Tanggetada based on (1) the implementation strategy of Kalo Sara values on the educator, (b) as a manager, (c) as an administrator, (d) as a supervisor, (e) as a leader, (f) as the one who Creates work climate, (g) as an entrepreneur; (2) the impact of the implementation of Kalo Sara values towards school management of the principal’s leadership consisted of (a) the principal as a driving force of management in school, (b) achievement of the objective of the institution which had been planned and conducted as the principal, teachers, and students; (3) the supporting and inhibiting factors of the implementation of Kala Sara values, sense of unity, friendship, and similarity of vision and mission, (a) the inhibiting factors: comprehension of all teachers on the important Kala Sara values, sense of unity, friendship, and similarity of vision and mission, (b) the supporting and inhibiting factors (internal) were lack of attention from the government in preserving Kalo Sara values and lack of partnership between the government and the school’s management in instilling Kalo Sara values on students;the inhibiting factors (external) were lack of attention from the society toward Kalo Sara values and modern life style of the society.